Evaluation of Broadcast Storm Mitigation Techniques on Vehicular Networks Enabled by WAVE or NDN - Gama, Óscar Sílvio Marques Almeida (2020)
A vehicle in a vehicular ad-hoc network (VANET) can perform wireless broadcasting by flooding to find a route to a node or to send an emergency warning, for example. However, this is usually a very demanding operation because it may originate broadcast storms, with high impact on redundancy and collision of packets, as well as channel bandwidth waste. Diverse strategies have been proposed by the research community to mitigate the broadcast storm problems. To contribute to this important topic, this work evaluates on a simulation scenario the network performance of a VANET in terms of content delivery time, signal-to-interference-plus-noise ratio (SNIR) packet loss and duplicate packets, considering the use of broadcasting by flooding on two prominent network paradigms: wireless access in vehicular environment (WAVE) and named data networking (NDN). Afterwards, these network technologies are used to study two distinct strategies to mitigate the flooding problems. One strategy uses a counter-based scheme and the other a geographic location scheme. Simulation results show that both strategies are effective in mitigating the broadcast storm problems in terms of the considered metrics.